Review of celiac disease in the pediatric population - Strawińska, Aleksandra; Wydro, Maria; Grotowska, Magdalena; Łukasiewicz, Martyna (Quality in Sport, 2025)
Celiac disease (CD) is a chronic autoimmune disease triggered by the ingestion of gluten in genetically predisposed individuals, primarily those with HLA-DQ2 and HLA-DQ8 haplotypes. The global prevalence of CD ranges from 0.5% to 1%. Recent advances in diagnostic methods and raising awareness of this disorder have improved detection rates, but many cases remain undiagnosed due to the disease's multifaceted presentation. CD can manifest with a wide range of symptoms, including both gastrointestinal and extraintestinal signs. In smaller children common symptoms include mainly chronic or intermittent abdominal pain, abdominal distension, diarrhea and constipation. Older children and adolescent patients may frequently present atypical, vague symptoms such as fatigue, failure to thrive, weight loss, short stature, behavioral changes and anemia. Diagnosis involves primarily serological tests in patients presenting symptoms or in patients with high-risk of developing CD. A strict gluten-free diet is the principal treatment and it is highly effective in managing symptoms and promoting intestinal healing. In this paper, we will analyze epidemiology of CD, its pathogenesis, heterogeneous clinical presentation, the diagnostic process and treatment based on recent guidelines and literature.